Preparation method of fluorine adsorbent, fluorine adsorbent obtained by preparation method and application of fluorine adsorbent
By loading Al4(PO4)x(OH)12-3x on WO3 spheres, the existing fluorine adsorption capacity, susceptibility to interference and low regeneration efficiency are solved, and high-efficiency and broad-spectrum fluorine ion capture and treatment effects are achieved.
Patent Information
- Application Number
- CN202411913891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing fluorine adsorbents have problems such as low adsorption capacity, susceptibility to coexistence ions, limited pH application range and low regeneration efficiency, making it difficult to achieve industrial application.
By loading Al4(PO4)x(OH)12-3x on WO3 spheres, the adsorption capacity, scope of application and regeneration efficiency of fluorine adsorbents are improved by leveraging the adsorption capacity, scope of application and regeneration efficiency of WO3 using the adsorption capacity of WO3 and the physical and chemical structural stability of Al4(PO4)x(OH)12-3x.
The high adsorption capacity, wide application range, high regeneration efficiency and long service life of fluorine adsorbents are achieved, and the capture and processing capacity of fluorine ions is significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to a fluorine adsorbent, in particular to a method for preparing a new fluorine adsorbent, and also to the fluorine adsorbent obtained by the preparation method and application of the fluorine adsorbent in treating fluoride ions in water. Background Art
[0002] Fluoride is widely present in surface water. According to my country's Drinking Water Standard (GB5749-2006), the fluoride concentration limit in drinking water cannot exceed 1.0 mg L -1 Existing methods for removing fluoride from water include precipitation, ion exchange, electrodialysis, membrane separation, adsorption and in-situ methods. Among them, adsorption is a method that uses porous materials to adsorb fluoride on the surface of solids to achieve the purpose of fluoride removal. It is a common method for removing fluoride from water and can reduce the fluoride concentration in water to 1 mg L -1 The following can reach the standard of drinking water, and it has the advantages of being economical and easy to operate. However, existing fluorine adsorbents generally have technical defects such as poor stability, low fluorine adsorption efficiency, and low adsorption capacity. For example, Chinese invention patent application CN 117816116A provides a method for preparing a defluorination adsorbent by modifying coal-based solid waste, wherein the coal-based solid waste and a portion of the defluorination active substance are ball-milled, an active coupling agent is added to react, and then the defluorination active substance is added to react. However, the adsorption capacity of the defluorination material is low, only about 0.49 mg / g.
[0003] Chinese invention patent application CN 117732420A provides a method for preparing a rare earth-based defluorination adsorbent, which adopts a complex precipitation method to obtain a sheet-like porous defluorination adsorbent by complexing lanthanum and cerium ions in the liquid phase with a complexing agent. However, the cost of lanthanum and cerium raw materials is relatively high, so the cost of industrial application of the defluorination adsorbent is relatively high. Similarly, Chinese invention patent application CN 117563557A provides a defluorination adsorbent and its preparation method and a defluorination method for lithium battery recovery liquid. However, a large amount of toxic and harmful organic raw materials or solvents are used in the synthesis process of this method, which is unfriendly to operators and the environment and difficult to promote.
[0004] Liu Jingdu et al. prepared nano-spherical perovskite LaAlO3 by coprecipitation-hydrothermal method in "Preparation of Nano-spherical LaAlO3 and Its Fluoride Removal Performance under Acidic Conditions". Under the condition of initial fluorine concentration of 200 mg / L, the adsorption capacity of LaAlO3 reached 53.8 mg / g in 8 minutes, and the equilibrium adsorption capacity reached 66.5 mg / g in 4 hours. With alum as desorbent, LaAlO3 can still maintain more than 90% of its original fluoride removal performance after 4 cycles, with good regeneration performance and practical utilization value. However, this defluoride adsorbent needs to be used in an acidic environment, so its application range is relatively narrow.
[0005] Through the analysis of existing technologies, it is found that existing defluorination adsorbents generally have the disadvantages of low adsorption capacity and susceptibility to interference from coexisting ions, or are difficult to apply industrially due to problems such as limited pH range and low regeneration efficiency. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a fluorine adsorbent with stable physical and chemical structure, high adsorption capacity, wide application range, high regeneration efficiency and long service life.
[0007] The idea of the present invention is to load Al4(PO4) on WO3 pellets. x (OH) 12-3x WO3 is used as the substrate to obtain the function of removing fluoride ions, and Al4(PO4) is used x (OH) 12-3x The powder has stable physical and chemical structure to increase the adsorption capacity of the substrate, broaden the scope of application and improve the regeneration efficiency.
[0008] Based on this, the present invention provides a method for preparing a fluorine adsorbent, the method comprising the following steps:
[0009] (1) Preparation of substrate
[0010] Tungsten trioxide and ammonium metatungstate are weighed according to the molar ratio of tungsten ions of 1:2 to 1:5, and tungsten trioxide, ammonium metatungstate and water glass are placed in a molding device for granulation to obtain a granular wet material with a diameter of 0.5 to 3 mm. The obtained wet material is sintered at 600°C to 900°C to obtain a granular substrate, wherein the amount of water glass is 10 to 20 times the total weight of tungsten trioxide and ammonium metatungstate;
[0011] (2) Primary modification
[0012] A phosphoric acid solution with a molar concentration of 1 to 3 mol / L is prepared, and a sodium hydroxide solution is added until the pH value is adjusted to 13 to 14 to obtain a mixed solution, and then the granular substrate obtained in step (1) is fully immersed in the mixed solution, and then taken out and dried to obtain primary modified particles;
[0013] (3) Secondary modification
[0014] The primary modified particles obtained in step (2) are fully immersed in an aqueous solution of aluminum chloride having a mass concentration of 20% to 60%, and then taken out and dried to obtain secondary modified particles;
[0015] (4) Post-processing
[0016] The obtained secondary modified particles are washed with water and dried to obtain a fluorine adsorbent.
[0017] In the present invention, the molding equipment in step (1) is a rotary disk molding machine. A rotary disk molding machine refers to a molding equipment in which the working part or molding piece of the machine rotates to make the material undergo plastic deformation to obtain a desired shape and size. For example, a rotary granulator produced and sold by Changzhou Lima Drying Technology Co., Ltd. is used to add tungsten trioxide, ammonium metatungstate and water glass to the material inlet to obtain granular wet materials.
[0018] Water glass (commonly known as sodium silicate) is a soluble alkali metal silicate material composed of alkali metal oxides and silicon dioxide, wherein the molecular formula of sodium water glass is Na2O·nSiO2, and the molecular formula of potassium water glass is K2O·nSiO2, which is usually in liquid form. According to a preferred embodiment, the modulus of the water glass in step (1) is 2.5-3.6, and the specific gravity of the water glass is 1.318-1.599 g / cm 3 The Baume degree of the water glass is preferably 34.98-54.32°Bé.
[0019] In the present invention, controlling the amount of water glass to 10 to 20 times the total weight of tungsten trioxide and ammonium metatungstate can ensure that the fluorine adsorbent finally obtained has a sufficiently high adsorption capacity and good strength. When the amount of water glass used is too much, exceeding 20 times the total weight of tungsten trioxide and ammonium metatungstate, the proportion of WO3 in the substrate will be too small, resulting in a decrease in the adsorption capacity of the adsorbent. When the amount of water glass used is too small, less than 10 times the total weight of tungsten trioxide and ammonium metatungstate, there is too little sticky material in the obtained granular wet material, and the strength of the adsorbent finally obtained after the substrate is treated in subsequent steps is too low, and it is easy to break or crush during use.
[0020] As a preferred embodiment, the molar concentration of the sodium hydroxide solution in step (2) is 2 to 4 mol / L.
[0021] In the present invention, step (2) fully soaking means that the solid phase material is completely immersed in the liquid phase. Generally, the volume of the solution should be not less than 1.5 times, preferably 1.5 to 3 times, of the granular substrate, and the soaking time is 8 to 24 hours to ensure that the surface of the granular substrate is fully attached to the sodium phosphate and disodium hydrogen phosphate. Similarly, step (3) fully soaking means that the volume of the solution should be not less than 1.2 times, preferably 1.2 to 1.5 times, of the granular substrate, and the soaking time is 12 to 24 hours to ensure that the material is fully in contact with the aluminum chloride aqueous solution.
[0022] Preferably, the drying temperature of step (2) is 100-150° C., and the drying temperature of step (3) is 150-200° C. In step (2), since a mixture of sodium phosphate and disodium hydrogen phosphate is attached to the surface of the granular substrate, in order to prevent disodium hydrogen phosphate from generating sodium pyrophosphate at high temperature, the drying control temperature of step (2) should be controlled in a relatively low range. In step (3), a higher temperature can be used to achieve rapid drying of the material.
[0023] The drying in step (4) is carried out at a constant temperature of 40 to 150° C. for 2 to 24 hours.
[0024] Al4(PO4) on the defluorination adsorbent obtained by the above method x (OH) 12-3x The free fluoride ions in the water are quickly captured, and the fluoride ions further diffuse on the WO3 substrate, thereby increasing the adsorption rate of the defluorination adsorbent.
[0025] Furthermore, the present invention also provides the use of the fluorine adsorbent obtained by the above preparation method in removing fluoride ions from water, which is particularly beneficial when the concentration of fluoride ions in water is less than 100 mg / L.
[0026] The present invention utilizes the good adsorption capacity of WO3 for fluoride ions, and using it as a substrate can greatly increase the adsorption capacity of the defluorination adsorbent for fluoride ions.
[0027] On the other hand, Al4(PO4) obtained by double modification x (OH) 12-3x The powder has a stable physical and chemical structure, high adsorption capacity, a wide pH range, and high regeneration efficiency. Al4(PO4) with rapid adsorption capacity for fluoride ions is loaded on the porous WO3 substrate. x (OH) 12-3x The material can realize the rapid capture of fluoride ions in water, improve the adsorption rate, and increase the amount of water treated per unit time.
[0028] The present invention utilizes Al4(PO4) x (OH) 12-3x The material has a rapid adsorption capacity for fluoride ions, first quickly capturing the fluoride ions in the water and gathering them in Al4(PO4) x (OH) 12-3x / WO3 pores, and then the base material WO3 is used to adsorb fluoride ions in large capacity. This coupling effect can realize Al4(PO4) x (OH) 12-3x / WO3 can not only quickly capture fluoride ions to make the fluoride ion concentration of produced water meet the standard, but also adsorb fluoride ions in large capacity, reduce the number of regeneration times, and increase the adsorption capacity of the adsorbent per unit volume and the amount of water treated. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The physical image and surface scanning electron microscope image of sample 1 of Example 1;
[0030] Figure 2 is the adsorption capacity of sample 1 of Example 1;
[0031] Figure 3 The physical image and surface scanning electron microscope image of sample 2 of Example 2;
[0032] Figure 4 is the adsorption performance of sample 2 of Example 2;
[0033] Figure 5 The physical image and surface scanning electron microscope image of sample 3 of Example 3;
[0034] Figure 6 This is the adsorption performance of sample 3 in Example 3. DETAILED DESCRIPTION
[0035] The following examples are used to explain the technical solutions of the present invention in a non-limiting manner.
[0036] In the present invention, unless otherwise specified, "%" used to describe concentration refers to weight percentage, and ":" refers to weight ratio.
[0037] Example 1
[0038] 7.3kg of water glass, 23kg of tungsten trioxide, and 50kg of ammonium metatungstate were added to the granulator turntable for granulation. The diameter of the granulator was 1.0m, the horizontal inclination of the granulator was 45°, and the speed of the granulator was 30r / min. After sintering at 650°C, a substrate with a diameter of 0.5mm was obtained. The granular substrate was immersed in a mixed solution of sodium hydroxide and phosphoric acid with a pH of 13 for 8 hours, and then taken out and dried.
[0039] The obtained material was immersed in 100L of 20% aluminum chloride aqueous solution for 12 hours, and then taken out and dried at 150° C. The dried granular material was washed with water and dried conventionally to obtain fluorine adsorbent sample 1.
[0040] The physical image and surface scanning electron microscope image of the obtained sample 1 are as follows: Figure 1 As shown, it can be seen that the adsorbent particles are relatively uniform and the particle surface is irregular.
[0041] Sample 1 was put into concentrated hydrochloric acid. The Al element and PO4 in the solution were tested by inductively coupled plasma spectrometer and ion chromatography. 3- The results of the element contents are shown in Table 1.
[0042] The test results in Table 1 confirm that the Al4(PO4) x (OH) 12-3x The chemical formula is Al4(PO4)3(OH)3.
[0043] The adsorbent was loaded into a glass column to form an adsorption column. The adsorption test was performed with a fluorine-containing test liquid of 20 mg / L (in terms of fluoride ions) at a flow rate of 20 BV / h using the over-flow method. The fluoride ion concentration in the test liquid before and after adsorption was recorded, and the adsorption capacity of the adsorbent per unit mass was calculated. After the adsorption capacity was saturated, the adsorbent was regenerated for 1 hour with a 2 mol / L sodium hydroxide solution at a flow rate of 8 BV / h. After the regeneration was completed, the adsorption test was repeated. Repeat 20 cycles.
[0044] The existing defluorination adsorbent on the market was used as a control.
[0045] The results are as follows Figure 2 As shown, the test confirmed that the saturated adsorption capacity of the adsorbent of the present invention for fluoride ions is 76 mg / g, which is significantly higher than 31 mg / g of Ti-SiO2 defluorination adsorbent purchased on the market. It proves that the defluorination adsorbent of the present invention has the performance advantage of high adsorption capacity.
[0046] Table 1 Chemical formula and adsorption capacity analysis of defluorination adsorbents
[0047]
[0048] It can be seen that the adsorbent of the present invention has a high adsorption capacity at this flow rate and good product stability.
[0049] Example 2
[0050] 7.5kg of water glass, 23kg of tungsten trioxide, and 87kg of ammonium metatungstate were added to the granulator turntable for granulation. The diameter of the granulator was 1.2m, the horizontal inclination of the granulator was 50°, and the speed of the granulator was 50r / min. After sintering at 750°C, granular seeds with a diameter of 2.0mm were obtained. The granular seeds were soaked in a mixed solution of sodium hydroxide and phosphoric acid with a pH of 14 for 12h, and then dried after being fished out at a drying temperature of 120°C. Then, the small balls were soaked in 150L of 40% aluminum chloride aqueous solution for 16h, and then dried after being fished out at a drying temperature of 170°C; the dried small balls were washed with water and dried to obtain defluorination adsorbent sample 2.
[0051] Figure 3 This is a physical picture of the defluorination adsorbent ball product and a surface scanning electron microscope picture. The defluorination adsorbent particles are relatively uniform. From the electron microscope photo, it can be seen that they have a cubic structure with a diameter of about 0.5 to 1 μm.
[0052] The Al4(PO4) of sample 2 was confirmed by the same method as in Example 1. x (OH) 12-3x The chemical formula is Al4(PO4) 3.6 (OH) 1.2 .
[0053] The saturated adsorption capacity of the adsorbent of this embodiment for fluoride ions is 84 mg / g, which is much higher than 31 mg / g of the defluorination adsorbent purchased on the market, proving that the defluorination adsorbent of the present invention has the performance advantage of high adsorption capacity.
[0054] Table 2 Chemical formula and adsorption capacity analysis of defluorination adsorbent
[0055]
[0056]
[0057] The same method as in Example 1 was used, except that the flow rate of the test solution was adjusted to 30 BV / h, the fluoride ion concentration in the test solution was about 100 mg / L, and after adsorption by the defluorination adsorbent, the results were as follows Figure 4 As shown, in the test of continuous operation for 30 days, the produced water concentration was always less than 1 mg / L, meeting the national emission standards.
[0058] Example 3
[0059] 7kg of water glass, 23kg of tungsten trioxide, and 120kg of ammonium metatungstate were added to the granulator turntable for granulation. The diameter of the granulator was 2.0mm, the horizontal inclination of the granulator was 40°, and the speed of the granulator was 20r / min. After sintering at 850°C, granular seeds with a diameter of 3.0mm were obtained. The granular seeds were soaked in a mixed solution of sodium hydroxide and phosphoric acid with a pH of 14 for 22 hours, and then dried after being fished out at a drying temperature of 150°C. Then, the small balls were soaked in 200L of 60% aluminum chloride aqueous solution for 24 hours, and then dried after being fished out at a drying temperature of 200°C; the dried small balls were washed with water and dried to obtain the defluorination adsorbent sample 3.
[0060] Figure 5 This is a physical picture of the defluorination adsorbent pellet product and a surface scanning electron microscope picture. The defluorination adsorbent particles are relatively uniform. From the electron microscope photo, it can be seen that they have a cubic structure with a diameter of about 0.2 to 0.5 μm.
[0061] The Al4(PO4) of sample 3 was confirmed by the same method as in Example 1. x (OH) 12-3x The chemical formula is Al4(PO4) 3.8 (OH) 0.6The same test as in Example 1 confirmed that the saturated adsorption capacity of the sample of this example for fluoride ions was 81 mg / g, which is much higher than 31 mg / g of the defluorination adsorbent on the market. This proves that the defluorination adsorbent of the present invention has the performance advantage of high adsorption capacity.
[0062] Table 3 Chemical formula and adsorption capacity analysis of defluorination adsorbent
[0063]
[0064] The same method as in Example 1 was used, except that the flow rate of the test solution was adjusted to 50 BV / h, the fluoride ion concentration in the test solution was about 50-60 mg / L, and after adsorption by the defluorination adsorbent, the results were as follows: Figure 6 As shown, during the 30-day test, the produced water concentration was less than 1 mg / L, meeting the national emission standards.
[0065] Comparative Example
[0066] Comparative Example 1: 7kg of water glass, 23kg of tungsten trioxide and 120kg of ammonium metatungstate are added to the turntable of the granulator for granulation. The diameter of the granulator is 2.0mm, the horizontal inclination angle of the granulator is 40°, the speed of the granulator is 20r / min, and after sintering at 850°C, a / WO3 defluorination adsorbent with a diameter of 3.0mm is obtained.
[0067] Comparative Example 2: 7kg of water glass, 23kg of tungsten trioxide, and 120kg of ammonium metatungstate are added to the rotating disk of a granulator for granulation. The diameter of the granulator is 2.0mm, the horizontal inclination of the granulator is 40°, and the speed of the granulator is 20r / min. After sintering at 850°C, a granular seed with a diameter of 5.0mm is obtained. The granular seed is soaked in a mixed solution of sodium hydroxide and phosphoric acid with a pH of 14 for 22h, and then dried after being fished out at a drying temperature of 150°C. Then, the small ball is soaked in 200L of 60% aluminum chloride aqueous solution for 24h, and then dried after being fished out at a drying temperature of 200°C; the dried small ball is washed with water and dried to obtain a defluorination adsorbent.
[0068] Comparative Example 3: 7kg of water glass, 25kg of tungsten trioxide, and 25kg of ammonium metatungstate are added to the granulator turntable for granulation. The diameter of the granulator is 2.0mm, the horizontal inclination of the granulator is 40°, and the speed of the granulator is 20r / min. After sintering at 850℃, a granular seed with a diameter of 3.0mm is obtained. The granular seed is soaked in a mixed solution of sodium hydroxide and phosphoric acid with a pH of 14 for 22h, and then taken out and dried at a drying temperature of 150℃. Then, the small ball is soaked in 200L of 60% aluminum chloride aqueous solution for 24h, and then taken out and dried at a drying temperature of 200℃; the dried small ball is washed with water and dried to obtain a defluorination adsorbent.
[0069] The saturated adsorption capacity of each sample for fluoride ions was confirmed by the same test as in Example 1, as shown in Table 4:
[0070] Table 4 Adsorption performance of comparative examples
[0071] Saturated adsorption capacity (mg / g) Comparative Example 1 17 Comparative Example 2 31 Comparative Example 3 39
[0072] It can be seen that the Al4(PO4) x (OH) 12-3x / WO3 small ball type defluorination adsorbent, Al4(PO4) loaded on WO3 small ball x (OH) 12-3x WO3 as the base material itself has the function of removing fluoride ions, Al4(PO4) x (OH) 12-3x The powder has a stable physical and chemical structure, high adsorption capacity, a wide pH range, and high regeneration efficiency. x (OH) 12-3x / WO3 greatly improves the adsorption capacity, adsorption stability and service life of the adsorbent.
Claims
1. A method for preparing a fluorine adsorbent, the method comprising the following steps: (1) Preparation of substrate Tungsten trioxide and ammonium metatungstate are weighed at a tungsten ion molar ratio of 1:2 to 1:5, and tungsten trioxide, ammonium metatungstate and water glass are placed in a molding device for granulation to obtain a granular wet material with a diameter of 0.5 to 3 mm. The obtained wet material is sintered at 600°C to 900°C to obtain a granular substrate, wherein the amount of water glass is 10 to 20 times the total weight of tungsten trioxide and ammonium metatungstate; (2) Primary modification A phosphoric acid solution with a molar concentration of 1 to 3 mol / L is prepared, and a sodium hydroxide solution is added to adjust the pH value to 13 to 14 to obtain a mixed solution, and then the granular substrate obtained in step (1) is fully immersed in the mixed solution, and then taken out and dried to obtain primary modified particles; (3) Secondary modification The primary modified substrate obtained in step (2) is fully immersed in an aqueous solution of aluminum chloride having a mass concentration of 20% to 60%, and then taken out and dried to obtain secondary modified particles; (4) Post-processing The obtained secondary modified particles are washed with water and dried to obtain a fluorine adsorbent.
2. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The molding equipment in step (1) is a turntable molding machine.
3. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The modulus of the water glass in step (1) is 2.5-3.6, the specific gravity of the water glass is 1.318-1.599 g / cm3, and the Baume degree of the water glass is 34.98-54.32°Bé.
4. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The molar concentration of the sodium hydroxide solution in step (2) is 2-4 mol / L.
5. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The step (2) of fully soaking means that the volume of the solution is not less than 1.5 times of the granular substrate, and the soaking time is 8 to 24 hours.
6. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The drying temperature of step (2) is 100-150°C.
7. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The sufficient soaking in step (3) means that the volume of the solution should be no less than 1.2 times of the primary modified substrate, and the soaking time is 12 to 24 hours.
8. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The drying temperature of step (3) is 150-200°C.
9. Use of the fluorine adsorbent obtained by the preparation method according to any one of claims 1 to 8 in removing fluoride ions from water.
10. The use according to claim 9, characterized in that The concentration of fluoride ions in water is less than 100 mg / L.
Citation Information
Patent Citations
Defluorination adsorbent, preparation method thereof and defluorination method of lithium battery recovery liquid
CN117563557A
Flaky porous defluorination adsorbent as well as preparation method and application thereof
CN117732420A
Defluorination adsorbent prepared from modified coal-based solid waste and preparation method thereof
CN117816116A
Method for preparing mesoporous WO3 / SBA-15 molecular sieve
CN101172240A
Modified HAP composite material for removing fluoride in water body as well as preparation method and application of the modified HAP composite material
CN111266080A